2002
DOI: 10.1007/s00421-002-0673-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between pre-landing activities and stiffness regulation of the knee joint musculoskeletal system in the drop jump: implications to performance

Abstract: The purpose of the present study was to investigate the interaction between the pre-landing activities and the stiffness regulation of the knee joint musculoskeletal system and the takeoff speed during a drop jump (DJ). Nine healthy male subjects performed a DJ test from the height of 50 cm. The surface electromyographic (EMG) activity of the vastus lateralis (VL) muscle was recorded to evaluate both the pre-landing and post-landing muscle activation levels. Simultaneous recording of the jumping motion and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Studies have shown that muscles become active prior to impact and that the nature of this pre-activation changes based on the height of the drop [10,11]. The pre-activation of muscles, specifically the co-contraction of antagonists, prior to impact is thought to function to stiffen the joints and may prevent limb collapse at impact [15]. The pre-activation of muscles may also function to increase the sensitivity of stretch receptors and prime the sensory feedback response of the limb after impact [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that muscles become active prior to impact and that the nature of this pre-activation changes based on the height of the drop [10,11]. The pre-activation of muscles, specifically the co-contraction of antagonists, prior to impact is thought to function to stiffen the joints and may prevent limb collapse at impact [15]. The pre-activation of muscles may also function to increase the sensitivity of stretch receptors and prime the sensory feedback response of the limb after impact [9].…”
Section: Discussionmentioning
confidence: 99%
“…Such tuning of muscle activity in anticipation of impact is not limited to humans and has been documented in non-human primates [12], cats [13] and most recently in toads [14]. The anticipatory recruitment of landing muscles has thus far been considered a critical mechanism for stiffening joints and preventing the collapse of limbs at impact [15]. However, a complementary function of anticipatory muscle recruitment may be to alter the operating length of the muscle prior to an active stretch.…”
Section: Introductionmentioning
confidence: 99%
“…Co-Contraction of flexor and trunk extensor muscles and lower extremity muscle increases rigidity and protection of lower extremity joint structures in a way that magnitude of many contact forces during landing increase trunk stiffness [41]. Iida et al (2011) reported that contact force has positive relationship with maximum voluntary contraction of rectus abdominis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed preactivation of the lower extremity [42][43][44] and trunk muscles [37,44] before contacting with the ground during landing. Okubo et al (2013) investigated abdominal muscles activities during the jump landing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have found that joint moments and kinematic variables can be used to predict, through linear regression analyses, the vertical height in which males jump (1,15). For example, men have exhibited that increased knee and hip extensor moments are correlated with an increased vertical jump height (1,15,18). This indicates that hip and knee extensor musculature strength may be critical components that could be targeted in a strength and conditioning program that aims to improve jumping performance.…”
Section: Introductionmentioning
confidence: 99%